Physiological and enzymatic changes in soybean seeds submitted to harvest delay - Zuffo, Alan Mario (2018)
Harvest delay may affect the physiological quality of soybean seeds due to the occurrence of unfavorable environmental conditions in the field. This study was conducted to investigate the physiological and enzymatic changes in soybean seeds submitted to harvest delay. A randomized block design, with eight seed harvest periods (0; 5; 10; 15; 20; 25; 30; and 35 days after the R8 phenological stage - full maturity) of the BRS 820 RR® cultivar, with four replicates, was used. At each harvest period, the moisture content, 1,000-seed weight, germination, seedling emergence, emergence speed index, accelerated aging, vigor and viability (tetrazolium test), electrical conductivity, enzymatic expression and seed yield were measured. Harvest delay up to 35 days after the R8 phenological stage do not affect the 1,000-seed weight and seed yield. The delayed harvest from the R8 stage results in increased damage by stink bugs and moisture. The harvest delay of seeds from the 10th day after the R8 stage impairs the seed vigor and, from the 15th day, seed germination. Seeds harvested with a delay after the R8 stage have lower expressions of the following isoenzymatic systems: malate dehydrogenase, alcohol dehydrogenase, esterase, isocitrate lyase and superoxide dismutase, especially after 15 days of harvest delay.